Algorithms or advocacy: does the legal profession have a future in a digital world?. Issue 1 (2nd January 2016) - Simpson, Brian
Abstract : Much of the focus on the impact of new technology on employment has been on work which is regarded as repetitive and requiring minimal skills. For the most part it seems that professional occupations have been assumed to be relatively immune to the effects of 'digital disruption'. However, there are now suggestions that this is altering as new software programs have been developed that can undertake at least some of the functions of various professions, including the legal profession. This article seeks to add to the evolving conversation of how new technologies might transform the legal profession as we know it. Beyond this, it also seeks to ask how the content of the law and legal education might also be affected by 'digital disruption', and explore the opportunities such unravelling of the legal profession might present.